An additive for edible oil composition. - Mohamed, Suhaila; Mohd Nor, Fatihanim (2007)

(untitled)
An extract derives from plant parts of Rutaceae plant family to be incorporated into a cooking oil composition for reducing oil absorption into food fried in the cooking oil composition thereof.